Common and different characteristics among combinations of physical frailty and sarcopenia in community‐dwelling older adults: The Korean Frailty and Aging Cohort Study. Issue 1 (23rd November 2021) - Lee, Daehyun; Kim, Miji; Won, Chang Won
Abstract : Aim: Physical frailty and sarcopenia are geriatric syndromes associated with adverse health outcomes. However, the common and different conditions associated with physical frailty and sarcopenia remain unclear. This study aimed to compare the clinical characteristics of older adults with physical frailty and sarcopenia. Methods: This cross‐sectional study analyzed 2028 community‐dwelling older adults, aged 70–84 years (mean age 75.9 ± 4.0 years; 50.1% men). Physical frailty was defined using the Fried frailty phenotype, whereas sarcopenia was defined using the Asian Working Group for Sarcopenia 2014 and 2019 criteria. Results: The prevalence of physical frailty was 5.5%, whereas that of sarcopenia, using the Asian Working Group for Sarcopenia 2014 and 2019, was 9.1% and 17.5%, respectively. The concordance of physical frailty with sarcopenia was higher in the Asian Working Group for Sarcopenia 2019 criteria than in 2014. Frail‐only participants had a higher incidence of disability, cognitive dysfunction, poor self‐perceived health, and depressive symptoms than the sarcopenic‐only participants. Frail‐and‐sarcopenic participants showed a lower body mass index (≥23 kg/m 2 ) than frail‐only participants. Furthermore, in frail‐and‐sarcopenic participants, recurrent falls (16.9% vs 5.5%) were higher than in the neither‐frail‐nor‐sarcopenic participants; falls with fracture (11.5% vs 1.7%) and fear of falling (59.0% vs 36.7%) were higher in frail‐and‐sarcopenic participants than in sarcopenic‐only participants. Conclusions: This study showed significant differences between physical frailty and sarcopenia among community‐dwelling older adults. Older adults with physical frailty and sarcopenia were more likely to have higher fall‐related outcomes than the others. Geriatr Gerontol Int 2022; 22: 42–49 .